Phytoremediation of Petroleum Products Contaminated Soil - O. I. Akpokodje; H. Uguru (Archives of Current Research International, 2019)
This study investigated the impact of petroleum products on the physiochemical properties, heavy metals and THC of soil samples; and their possible phytoremediation. Perforated plastic buckets were filled with 10 kg of sieved virgin topsoil. A mixture of 2 L of spent engine oil, 2 L of kerosene, 2 L of petrol and 2 L of diesel was gradually poured into each bucket and allowed to drain through the soil, once a day for five days, and there after left to stabilize for a period of 21 days. Fluted pumpkin (Telforia Occidentalis) and Okra (Abelmoschus esculentus, Cv. Kirikou) seeds were planted in buckets and closely monitored for 14 weeks. Soil analysis of the virgin topsoil, contaminated soil and remediated soil was done using standard methods. Tests results showed that the petroleum products significantly (p ≤0.05) altered the physicochemical properties, heavy metals and THC of the soil. From the results, the soil porosity decreased from 35% to 14%; specific gravity decreased from 2.34 to 1.35; the soil pH decreased from 7.05 to 5.34; the THC increased from 0,923 mg/kg to 964.35 mg/kg; copper level increased from 4.892 mg/kg to 7.729 mg/kg; the lead content increased from <0.0001 mg/kg to 1.128 mg/kg; while the iron content increased from 1251.2 mg/kg to 1587.9 mg/kg after the contamination. After the 14 weeks phytoremediation period, Telfairia occidentalis was able to degrade the THC in the soil from 964.35 mg/kg to 82.67 mg/kg; while Abelmoschus esculentus degraded the THC in the soil from 964.35 mg/kg to 104 mg/kg. Therefore, due to the harmful effects of the petroleum products on agricultural soils, laws banning their indiscriminate disposal of should be enforced.